Practical and technical key challenges in head and neck adaptive radiotherapy: The GORTEC point of view. (May 2023) - Delaby, Nolwenn; Barateau, Anaïs; Chiavassa, Sophie; Biston, Marie-Claude; Chartier, Philippe; Graulières, Eliane; Guinement, Lucie; Huger, Sandrine; Lacornerie, Thomas; Millardet-Martin, Corinne; Sottiaux, Alain; Caron, Jérôme; et al.
Highlights: Overview of Head and Neck adaptive radiotherapy key steps. Presentation of adaptive radiotherapy tools and workflows. Practical recommendations for H&N adaptive radiotherapy. Challenges of H&N ART and current difficulties or limitations. Abstract: Anatomical variations occur during head and neck (H&N) radiotherapy (RT) treatment. These variations may result in underdosage to the target volume or overdosage to the organ at risk. Replanning during the treatment course can be triggered to overcome this issue. Due to technological, methodological and clinical evolutions, tools for adaptive RT (ART) are becoming increasingly sophisticated. The aim of this paper is to give an overview of the key steps of an H&N ART workflow and tools from the point of view of a group of French-speaking medical physicists and physicians (from GORTEC). Focuses are made on image registration, segmentation, estimation of the delivered dose of the day, workflow and quality assurance for an implementation of H&N offline and online ART. Practical recommendations are given to assist physicians and medical physicists in a clinical workflow.